(untitled) (Abstracta, 2023)
Artigos publicados - P009-2023 à P040-2023 Artigos aceitos - A01-2023 Correções - C01-2023 Defesas de Dissertações do IFGW - D002-2023 à D004-2023 Defesas de Teses do IFGW - T003-2023